Inheritance Child Out of Wedlock in The Compilation Of Islamic Law (KHI) Perspective And Civil Law (Burgerlijk Wetboek) - Yuni Hastuti Tatarhati; Akhmad Khisni (Jurnal Akta, 2019)
This study aims to determine the position of the beneficiary 1. child out of wedlock in perspective Compilation of Islamic Law and the Civil Law (Burgerlijk Wetboek). 2. similarities and differences in the position of heir child out of wedlock in perspective Compilation of Islamic Law and the Civil Law (Burgerlijk Wetboek). The methods used include normative juridical approach with a qualitative descriptive study specifications. The method of data collection is literature study / documentary study of the primary legal materials, secondary law and tertiary legal materials by using qualitative analysis. The results of the study showed that notch that the child outside the mating according to KHI only have a relationship of inheritance with her birth mother, while according to Article 272 of the Civil Law can be seen that in the Civil Law there are children who do recognition and can be passed that Natuurlijk Kind, and there is also a child that can not be done against the overspeleg kind of recognition and blodsceneg. With the recognition that there arose a civil relationship between children and parents outside mating admit as stipulated in Article 280 of the Civil Law. Equal status illegitimate children in the perspective of the KHI and Civil Law is equally no right of inheritance. The difference is the inheritance rights of children outside of marriage can be granted if there is recognition of illegitimate children Natuurlijk just kind only. Meanwhile, according to KHI just recognition of extramarital children who have a religious marriage that can be recognized.Keywords: Inheritance; The position of heir; A child out of wedlock.